Multiproduct mine output and the case of mining waste utilization - Packey, Daniel (Pergamon, 2012)
This article addresses the concepts of economies of scope and multiproduct production, subadditivity and transray convexity as it applies to the mining industry. The article goes on to expand these concepts to include the case of mining waste utilization. It discusses how the modification of mining wastes into a marketable product can develop a relationship across the cost functions of the modified mining waste and ore production and how this interrelationship affects the profit maximizing condition. It discusses four possible outcomes from mining waste modification and its development into marketable products on the profitability and production of ore by the firm. Finally, it discusses mining waste utilization effects on rehabilitation costs and the potential for a decrease in the adverse community effects due to mine closure.